RELASI ONTOLOGIS BAHASA DAN SAINS: QUO VADIS FILSAFAT ILMU DI ERA DISRUPSI ARTIFICIAL INTELLIGENCE - Yudhi Hertanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to reconstruct the dialectical relationship between language and science in the midst of digital technological disruption, particularly the rapid development of Generative Artificial Intelligence (AI). In science, language functions not only as a means of communication but also as an ontological foundation that shapes the reality and validity of scientific knowledge. This research employs a qualitative approach through library research and philosophical hermeneutic analysis of literature in the philosophy of science, philosophy of language, and contemporary studies on AI. The analysis focuses on the role of terminology in the construction of knowledge, the demarcation between natural sciences (Naturwissenschaften) and social sciences and humanities (Geisteswissenschaften), and the future direction of the philosophy of science in responding to epistemic challenges in the AI era. The findings indicate that the stability of scientific terminology is experiencing a crisis due to AI hallucinations and paper mill practices that produce fake scientific works. At the same time, there is a shift in language games from descriptive to performative functions, as reflected in the use of the term “Global Boiling.” This study concludes that an adaptive epistemology is necessary to safeguard the integrity and validity of scientific knowledge in the algorithmic era. ABSTRAK Kajian ini bertujuan merekonstruksi relasi dialektis antara bahasa dan ilmu pengetahuan di tengah disrupsi teknologi digital, khususnya perkembangan Generative Artificial Intelligence (AI). Bahasa dalam sains tidak hanya berfungsi sebagai alat komunikasi, tetapi juga sebagai fondasi ontologis yang membentuk realitas dan validitas pengetahuan ilmiah. Penelitian ini menggunakan pendekatan kualitatif melalui studi kepustakaan dan analisis hermeneutika filosofis terhadap literatur filsafat ilmu, filsafat bahasa, serta kajian mutakhir tentang AI. Fokus kajian meliputi peran terminologi dalam konstruksi pengetahuan, demarkasi antara ilmu alam (Naturwissenschaften) dan ilmu sosial-humaniora (Geisteswissenschaften), serta arah masa depan filsafat ilmu dalam merespons tantangan epistemik era AI. Hasil penelitian menunjukkan bahwa stabilitas terminologi ilmiah mengalami krisis akibat fenomena halusinasi AI dan praktik paper mills yang memproduksi karya ilmiah palsu. Di sisi lain, terjadi pergeseran permainan bahasa dari fungsi deskriptif ke performatif, sebagaimana tercermin dalam istilah “Global Boiling”. Penelitian ini menyimpulkan perlunya epistemologi adaptif guna menjaga integritas dan validitas ilmu pengetahuan di era algoritmik.